O estudo do controle aversivo no Brasil com base em teses e dissertações: uma perspectiva histórica - Santos, Bruna Colombo dos (2012)
Aversive control is a controversial domain inside Behavior Analysis. Classically, includes negative reinforcement (escape and avoidance) and punishment. However, the nomenclature aversive control is used to refer to a number of other behavioral phenomena (conditioned suppression, learned helplessness, etc.). Because it is a controversial domain, in theoretical and experimental areas, reveals itself as a significant issue for historical studies. It was not found a brazilian historical study that has taken the production on aversive control in the country as an object of study. Thus, this work had two objectives: (1) to characterize the researches about aversive control in Brazil, through the analysis of theses and dissertations produced in the country; (2) to analyze the researches on negative reinforcement (escape and avoidance), punishment and aversive control (researches that dealt with the issue in general), the point of view of definitions proposed, terminology used to refer to aversive events, main results, byproducts and application considerations about by-products and to application. To achieve these objectives, two studies were conducted. For the Study 1, were selected theses and dissertations between 1968 and 2010 in the following sources: Database of dissertations and theses in Behavior Analysis (BDTAC/Br); Brazilian Universities digital libraries; Bank of theses and dissertations from CAPES; and Lattes curricula. 98 theses and dissertations on aversive control were found. The universities where more studies were produced were: USP, PUC-SP, UnB, UFPA, USP-RP, and UEL. The vast majority of work was the basic type on uncontrollability/ learned helplessness. The subject more used was the rat; and aversive stimulus, the electric shock. For the Study 2, were selected, based on reading the abstracts of theses and dissertations selected for the Study 1, theses and dissertations on punishment, negative reinforcement (escape and avoidance) and aversive control. It were analyzed the definitions used, the authors in which this definition was based on, the terminology used to refer to events presented in aversive contingencies, the main results found, by-products and considerations for application. Punishment definitions of varied types were found: operational/positive; operational positive/negative; operational/positive and processual; operational/ positive and negative and processual; operational and processual. The definitions of negative reinforcement avoidance were: definitions of responses or avoidance behavior; definitions of avoidance procedures. The definitions about negative reinforcement in general encompassed the escape and avoidance process. The definitions of aversive control included negative reinforcement and punishment. Different authors were used in the definitions, and many have not cited authors. The most used term was aversive stimulus. Regarding the results it was observed variability, due to different research problems and methods. The works on aversive control in general were the ones that most discussed by-products and application